Poverty squares and gender circles: unravelling agriculture gaps, challenges and opportunities in the Eastern Gangetic Plains - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Research was conducted in 4 villages in Jalpaiguri District where two major development initiatives are implemented. One initiative, Anandadhara (National Rural Livelihoods Mission), aims for a convergence of social and economic empowerment by enabling women to form self- managed, federated self-help groups (SHGs). In addition to enabling access to savings and credits, these women’s collectives aim to facilitate knowledge of and access to rights, entitlements and public services. The other is World Bank funded Accelerated Development of Minor Irrigation (ADMI), which aims to increase agricultural incomes of small / marginal farmers through improved access to irrigation water. This includes minor irrigation schemes - solar or diesel pumps, training on improved and diversified crop farming and marketing, and strengthening water user associations (WUA), with a focus on women’s participation.